2021
DOI: 10.1016/j.spinee.2020.10.008
|View full text |Cite|
|
Sign up to set email alerts
|

Spinal manipulation and perineural electrical dry needling in patients with cervicogenic headache: a multicenter randomized clinical trial

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 74 publications
(59 reference statements)
0
19
0
Order By: Relevance
“…The RoB analysis showed high inter-rater reliability (Cohen’s Kappa = 0.87). Overall RoB was low in eight trials [ 53 , 55 , 56 , 60 , 61 , 66 68 ], unsure in six trials [ 51 , 58 , 62 64 , 69 ], and high in six trials [ 52 , 54 , 57 , 59 , 65 , 70 ] for the primary and secondary outcome measures. Further detail regarding the RoB of individual studies is found in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The RoB analysis showed high inter-rater reliability (Cohen’s Kappa = 0.87). Overall RoB was low in eight trials [ 53 , 55 , 56 , 60 , 61 , 66 68 ], unsure in six trials [ 51 , 58 , 62 64 , 69 ], and high in six trials [ 52 , 54 , 57 , 59 , 65 , 70 ] for the primary and secondary outcome measures. Further detail regarding the RoB of individual studies is found in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Although physiotherapy with dry needling and electrical dry needling has proven positive effects on chronic low back pain [ 22 31 ], the results of studies into the duration of the analgesic effect and the dose required, for example, are contradictory [ 61 , 62 ]. Therefore, further research is required to evaluate the specific components of the treatments administered by physical therapists.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Dry needling is typically used to treat soft tissues, such as muscles, ligaments, tendons, fascia, scar tissue, peripheral nerves and neurovascular bundles involved in a variety of neuromusculoskeletal pain syndromes [ 21 , 22 ]. Dry needling involves the insertion of fine monofilament needles without the use of injectables, and its therapeutic effect is based on stimulating specific reactions in the target tissue [ 23 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 7 , 8 ] Among them, acupuncture and massage as a part of traditional Chinese medicine therapy have gradually become the research hotspot [ 8 ] of treating this disease because of their advantages of loosening adhesion, effectively relieving muscle spasm, reducing pain and local pressure, and small side effects. Multiple traditional studies [ 9 12 ] have confirmed the significant clinical efficacy of acupuncture or massage in CGH, based on this, we explore whether acupuncture combined with massage has better efficacy compared with other therapies. In this study, the purpose of this systematic review was to assess the effectiveness and safety of acupuncture combined with massage for CGH and to provide evidence for clinical decision-making.…”
Section: Introductionmentioning
confidence: 99%